Using Picture-Series-On-Instagram to Improve Students’ Narrative Writing Skills at A Public Senior High School in Kampar - Riza Amelia; Harum Natasha; Ulfaturrahman (Milenial: Journal for Teachers and Learning, 2023)
Instagram app allows its users to tell their stories worldwide through publishing their images which are sometimes accompanied by some verbal description of the texts. This study aims to find out if picture-series-on-instagram app can be used as a learning tool in the classroom to improve students’ writing ability on narrative text type. The design of the present research was quasi-experimental. The population of the research was the tenth-grade students of a public senior high school in Kampar. Two classes were selected as the experimental and controlled classes. The total number of both classes was ninety students. Data collection technique was a pre-test and post-test of writing a narrative text. The results of test were scored by two experts as the raters whereas a writing assessment rubric by Brown (2007) was employed as the reference. Data analysis technique of the research used an independent t-test formula to compare the post-test results from the experimental and the controlled classes. The findings found that the post-test results of the experimental students were significantly higher compared to post-test results of the controlled students (Sig, 2-tailed = 0.039 < 0.05). As a conclusion, the use of the picture-series-on-instagram app was shown to significantly more effective to improve students’ ability to write a narrative text than the use of the conventional method. The findings of this present research support the findings of the previous studies that the picture-series is instrumental to improve the EFL students’ writing ability on narrative texts. Furthermore, it is recommended that the use of picture-series to improve students’ writing ability on narrative text could be used by the tenth-grade teachers in their classrooms.